METODE KETELADANAN GURU DALAM MENANAMKAN SIKAP MANDIRI PADA ANAK DI TADIKA BESTARI IMPIAN AL-FIKH ORCHARD BUKIT MERTAJAM PENANG, MALAYSIA - fairuz soraya; Rizka Harfiani (al-Iltizam: Jurnal Pendidikan Agama Islam, 2026)
Abstract: This research was conducted to examine the implementation of the teacher modeling method for fostering independence early childhood students at Tadika Bestari Impian Al-Fikh Orchard, Bukit Mertajam, Penang, Malaysia. The research employed a descriptive qualitative research approach. Data collection was carried out through observation, interview sessions, then analyzed using the interactive data analysis framework developed by Miles, Huberman, and Saldaña, which consists of data collection, data condensation, data display, and drawing conclusion. The findings indicated that the modeling method was regularly implemented through direct demonstration, daily habituation activities, self-care skills development, assignment of responsibilities, and positive reinforcement. Supporting factors included a conducive learning environment, the teacher serving as a facilitator, structured daily routines, as well as positive support for children. Meanwhile, inhibiting factors included children's dependence on teachers, overprotective parenting styles, differences in developmental levels, and low self-confidence. Therefore, the teacher modeling method has proven effective in fostering independent behavior among early childhood learners.